Wave climate and extremes on a mesotidal atoll lagoon (Ocean and Coastal Research, 2022)
Processes on atolls and coral reef lagoons are defined by local wave and tide climates. Based on the reconstruction of lagoon wave climate by downscaling offshore historical wave information, this study aims to assess the wave climate and wave extremes on a mesotidal atoll lagoon (Rocas Atoll, Brazil). Results show that the transformation of offshore waves, when propagating into the lagoon, results in a different and far more homogeneous wave climate. Atoll morphology and tides play a key role in controlling the directional and energy characteristics of the lagoon wave climate. Refraction processes and the reef passage make the side protected from the dominant SE waves the most energetic zone for lagoon wave propagation. Lagoon waves tend to propagate in opposite directions to offshore wind waves, showing the refraction effect of approaching waves when crossing the atoll rim and the channel. The tidal effect on the dissipation process is also a filter for extreme wave conditions. We highlight the dependence of the resulting lagoon wave climate on atoll morphology, thereby addressing its implications to geomorphological process inside the atoll.